2012
DOI: 10.1155/2012/735078
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Insomnia Using the Traditional Chinese Medicine System: A Systematic Review

Abstract: A systematic review was conducted to examine traditional Chinese medicine (TCM) patterns commonly diagnosed in subjects with insomnia and clinical features associated with the TCM patterns, and an insomnia symptom checklist for TCM diagnostic purpose was developed based on the review. Two independent researchers searched the China Academic Journals Full-Text Database and 10 English databases. A total of 103 studies and 9499 subjects were analyzed. There was a wide variation in terminology relating to symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 14 publications
1
32
0
2
Order By: Relevance
“…To further examine pattern-based TCM therapies, a standardized and reliable TCM pattern differentiation procedure should be explored. We have recently developed a standardized symptom checklist for TCM pattern differentiation in patients with insomnia [29]. The diagnostic tool, consisting of 13 sleep-related, 61 nonsleep-related, 11 tongue, and 7 pulse items, can be further validated for TCM diagnostic purpose.…”
Section: Discussionmentioning
confidence: 99%
“…To further examine pattern-based TCM therapies, a standardized and reliable TCM pattern differentiation procedure should be explored. We have recently developed a standardized symptom checklist for TCM pattern differentiation in patients with insomnia [29]. The diagnostic tool, consisting of 13 sleep-related, 61 nonsleep-related, 11 tongue, and 7 pulse items, can be further validated for TCM diagnostic purpose.…”
Section: Discussionmentioning
confidence: 99%
“…3 TCM diagnosis was formulated with the help of a 92-item symptom checklist specially designed for the TCM diagnosis of insomnia. 4 Of 252 participants who received acupuncture or acupuncture plus auricular acupuncture, 205 subjects (81.3%) met criteria for one of the four most common TCM diagnoses and had 1 week post-treatment data. Acupuncture points used included bilateral ear Shenmen, Sishencong, PC6 Letters (Neiguan), HT7 (Shenmen), SP6 (Sanyinjiao), Yintang and GV20 (Baihui).…”
Section: Methodsmentioning
confidence: 99%
“…The research ethic approval (Additional file 1 ), research protocol (Additional file 2 ), and patient informed consent form (Additional file 3 ) are listed as additional files in this article. We used the Chinese Medicine Insomnia Symptom Checklist (Additional file 4 ) which was developed based on our previous systematic review [ 21 ], to systematically collect clinical data from the participants. In our previous review, we summarized the manifestation profiles reported in 103 studies on CM syndromes in participants with insomnia and identified 52 sleep-related symptoms, 169 non-sleep-related symptoms, 19 tongue features, and seven pulse signs that were described in the 10 most common CM syndromes.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the CM syndrome connotations of the latent variables, one author (WFY), who is a registered CM practitioner, consulted with another author (SPZ) to compare the clinical feature variables identified under each latent variable with the clinical features described in the 10 most common CM syndromes associated with insomnia, as summarized in a previous systematic review [ 21 ]. However, as this was the first-step of LTA to explore the co-occurrence pattern in a clinical sample with insomnia, we did not validate or compare the results with other non-LTA models.…”
Section: Methodsmentioning
confidence: 99%